Eu em cena: dramatizações da subjetividade em Ana Cristina Cesar e Paulo Henriques Britto - Silva, Elvis Barbosa Caldeira (2024)
This work aims to analyze the configuration of the lyric subject in Ana Cristina Cesar and Paulo Henriques Britto through the dramatization of the effect of subjectivity in their poetry. The dramatization or the way in which the two authors perform in their poems the impression of subjectivity of the “lyric-self”, persona placed to enunciate in the poem, is engendered through the intersection between language, otherness, and fictionalized biographical elements. To propose a deep investigation about the lyric subject as an issue, starting from modern and contemporary poetry, it is essential the exhibition of a brief journey. From Charles Baudelaire to Fernando Pessoa, going through Brazilian modernism towards Brazilian poetry from 1970 onwards, this work proposes an examination of the formation of the lyric subject in the light of theoretical proposals that critically retake the poetic enunciation and the relations between author, work, and reader in contemporary poetry. On the formation of the effect of subjectivity in modern and contemporary Brazilian poetry, as well as on the critical retake about the lyric subject, we have works by Annita Costa Malufe (2006, 2009, 2022), Celia Pedrosa (2014, 2015, 2018), Eduardo Veras (2020, 2022), Flora Süssekind (1993, 2004, 2007), Marcos Siscar (2011, 2016, 2023), Michel Collot (2018) and Viviana Bosi (2021) and other researchers.